Large shocks in menu cost models - Peter Karadi; Adam Reiff (European Central Bank (ECB), 2012)
How do prices react to large aggregate shocks? Our new micro-data evidence on value-added tax changes shows that prices react (i) flexibly and (ii) asymmetrically to large positive and negative shocks. We use it to quantitatively evaluate the performance of prominent pricing models. We show that standard time-dependent models are unable to reproduce either of these facts. A realistically calibrated state-dependent menu cost model, in contrast, is successful in matching the observed price responses. Its success lies in its ability to capture the exploding fraction of price changes for large shocks. The evidence facilitates comparison of different menu cost models and raises doubts on alternative pricing models with information or search frictions as sole reasons for price rigidity.
Keywords: E31; E52; 330; Inflation asymmetry; state-dependent pricing; time-dependent pricing; value-added tax shock